UJI AKTIVITAS REPELAN LOTION EKSTRAK ETANOL KULIT BUAH LANGSAT (Lansium parasiticum Osbeck.) TERHADAP NYAMUK Aedes aegypti - Pebrianti Pebrianti; Yusriadi Yusriadi; Ingrid Faustine (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Repellents are substances that can provide protection from nuisance insects by interfering with its sensory function. Lanzones fruit is known to contain triterpenoids which have activity as repelan. This study was to examine the repellent activity and to determine protection capacity of lotion containing ethanol extract of lanzones (Lansium parasiticum) peel against  Aedes aegypti mosquitoes. The ethanol extract was obtained by macerating the peel with 96% ethanol. The lotion is prepared in three extract concentrations, 15%; 20%; and 25% followed by its physical stability evaluation and activity examination. Data of pH, viscosity and dispersive capacity evaluation obtained were statistically analyzed using paired samples t-test. The results showed that the lotion preparations are stable on organoleptic observation and homogeneity evaluation. The statistical analysis of pH, viscosity, and the dispersive capacity evaluations showed that their results are significantly different after day 0 to day 28 storage (p> 0.05). Repellent activity examination of the lotion was carried out for 4 hours, using the Aedes aegypti mosquitoes. Of the three concentrations examined, each concentration has different repellent activity that concentration of 15% and 20% indicated a 100% protection up to 1 minute, and concentration of 25% indicated up to 135 minutes